Python Data Analysis Perform Data Collection, Data Processing, Wrangling, Visualization, and Model Building Using Python - Navlani, Avinash (Packt Publishing, Limited, 2021)
Data analysis enables one to generate value from small and big data by discovering new patterns and trends. Python is a popular tool for analyzing a wide variety of data. This books instructs how to get up and running with using Python for data analysis by exploring the different phases and methodologies used in data analysis and learning how to use modern libraries from the Python ecosystem to create efficient data pipelines.